Tailoring Renal Clearance and Tumor Targeting of Ultrasmall Metal Nanoparticles with Particle Density - Tang, Shaoheng (Angew Chem Int Ed Engl, 2016)
Identifying key factors that govern in vivo behaviors of nanomaterials is critical to future clinical translation of nanomedicines. Shadowed by size-, shape- and surface-chemistry effects, the impact of particle core density on clearance and tumor targeting of inorganic nanoparticles (NPs) remains largely unknown. By utilizing a class of ultrasmall metal NPs with the same size and surface chemistry but different densities as model, we found that both renal clearance and passive tumor targeting of the NPs are strongly correlated with their densities: with the decrease of particle density, renal-clearance efficiency exponentially increased in the early elimination phase but passive tumor targeting was linearly decreased. Through systematic investigation on their pharmacokinetics, biodistribution and kidney filtration, we found that lower density NPs more easily distribute in the body and have shorter retention in highly permeable organs such as kidneys than the higher ones. These density-dependent in vivo behaviors are likely due to the fact that high-density AuNPs marginated to the blood vessel walls more quickly than low-density NPs; as a result, they circulated slowly in the laminar blood flow than the low-density ones. These new findings highlight the importance of particle density in tailoring of in vivo behaviors of engineering NPs and might open up a new pathway for designing nanomedicines with desired functionalities together with other key factors.